Development and Characterization of Terbinafine-Loaded Nanoemulgel for Effective Management of Dermatophytosis - Mayank Phagna; Reena Badhwar; Manvi Singh; Abdulsalam Alhalmi; Rahmuddin Khan; Omar M. Noman; Ahmad Alahdab (Gels, 2023)
Dermatophytosis, the most prevalent fungal infection, is witnessing a rising incidence annually. To address this challenge, we developed a terbinafine-loaded oil-in-water nanoemulsion (TH-NE) through the aqueous microtitration method. The formulation comprised olive oil (oil phase), Span 80 (surfactant), and propylene glycol (co-surfactant). Pseudo-phase ternary diagrams and thermodynamic studies underscored the stability of TH-NE. Employing the Box–Behnken design (BBD), we optimized TH-NE, which resulted in a remarkable particle size of 28.07 nm ± 0.5, a low polydispersity index (PDI) of 0.1922 ± 0.1, and a substantial negative zeta potential of −41.87 mV ± 1. Subsequently, TH-NE was integrated into a 1.5% carbopol matrix, yielding a nanoemulgel (TH-NEG). Texture analysis of TH-NEG demonstrated a firmness of 168.00 g, a consistency of 229.81 g/s, negative cohesiveness (−83.36 g), and a work of cohesion at −107.02 g/s. In vitro drug release studies revealed an initial burst effect followed by sustained release, with TH-NEG achieving an impressive 88% release over 48 h, outperforming TH-NE (74%) and the marketed formulation (66%). Ex vivo release studies mirrored these results, with TH-NEG (86%) and TH-NE (71%) showcasing sustained drug release in comparison to the marketed formulation (67%). Confocal microscopy illustrated that TH-NEG and TH-NE penetrated to depths of 30 µm and 25 µm, respectively, into the epidermal layer. Furthermore, dermatokinetic studies highlighted the enhanced drug penetration of TH-NEG compared to TH-NE through mouse skin. In summary, our study establishes TH-NEG as a promising carrier for terbinafine in treating dermatophytosis, offering improved drug delivery and sustained release potential.